2009
DOI: 10.4103/0973-8398.49172
|View full text |Cite
|
Sign up to set email alerts
|

Microemulsion-based hydrogel formulation for transdermal delivery of dexamethasone

Abstract: T he purpose of this study was to construct a microemulsion-based hydrogel formulation for the transdermal delivery of dexamethasone. Almond oil, olive oil, linseed oil, and nutmeg oil were screened as the oil phase. A microemulsionbased system was chosen due to its good solubilizing capacity and skin permeation capabilities. The pseudoternary phase diagrams for microemulsion regions were constructed using various oils, egg lecithin as the surfactant, isopropyl alcohol (IPA) as the cosurfactant, and distilled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 23 publications
0
9
0
2
Order By: Relevance
“…The selected ME was o/w type, and this was in accordance with previous studies. It was reported that o/w ME type showed high conductivity in the range of 10-100 μS/cm while w/o type showed lower conductivity levels (32,40,41). For the stability test, the HPLC peak of OR did not show any degradation peaks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The selected ME was o/w type, and this was in accordance with previous studies. It was reported that o/w ME type showed high conductivity in the range of 10-100 μS/cm while w/o type showed lower conductivity levels (32,40,41). For the stability test, the HPLC peak of OR did not show any degradation peaks.…”
Section: Discussionmentioning
confidence: 99%
“…This may be affected by the ME formula with a permeation enhancer in reducing the diffusion barrier (32,40,41). As a commonly used transdermal enhancer, isopropyl myristate has been supposed to be able to increase permeation by fluidizing intercellular lipids in the stratum corneum or to increase drug solubility at the lipid part of the stratum corneum (42,43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, the capacity of the ME to solubilize large amounts of lipophilics drugs can be advantageous as well. 16 The dispersed phase of a ME, aqueous or lipidic (o/w or w/o types) potentially serve as reservoir of both water-soluble and fat-soluble drugs which may be partitioned in external and internal phases. 13 Various techniques have been employed to study the size, shape and interactions of ME droplets.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the same group described that Transfersomes ® with DEX and hydrocortisone were able to deliver the drug to viable skin layers allowing the reduction of the required dose 4 to maintain its efficacy compared to conventional vehicles [20]. More recently, Chandra, Sharma & Irchhiaya [21] developed microemulsions prepared with several oils and lecithin as surfactant and isopropyl alcohol as co-surfactant for transdermal delivery of DEX. Formulation based on olive oil showed the best in vitro drug permeation, while the microemulsion based on nutmeg oil showed higher in vivo anti-inflammatory activity.…”
mentioning
confidence: 99%